Corrigendum to: “Monitoring of Post-fire Vegetation Succession on Peat Ecosystem Area in Bengkalis Island, Riau Province” [Media Konservasi, Vol 30 Issue 3, 2025, DOI: 10.29244/medkon.30.3.423] - Pudjawati, Nihawa Hajar; Pulunggono, Heru Bagus; Asy’Ari, Rahmat; Zulfajrin, Moh; Nurazizah, Lina Lathifah; Saputri, Hanum Resti; Rivai, Fathan Aldi; Setiawan, Yudi (Media Konservasi, 2025)
This corrigendum corrects errors in the previously published article.